Do Participants Detect Sexual Abuse Depicted in a Drawing? Investigating the Impact of Betrayal Trauma Exposure on State Dissociation and Betrayal Awareness. Issue 3 (3rd April 2017) - Gobin, Robyn L.; Freyd, Jennifer
ABSTRACT: An inability to identify betrayal may increase risk for victimization. Harm perpetrated by close others early in life may impair the ability to identify betrayal and develop trust. Dissociation may facilitate impaired betrayal awareness. The present study examined the impact of high betrayal trauma on state dissociation and betrayal awareness in a college sample (N = 216). Self-report measures were used to assess trauma history and state dissociation. Awareness for betrayal was measured using a drawing depicting an ambiguous interpersonal interaction between an adult and a child. We hypothesized that high betrayal trauma would be associated with both more state dissociation and lower awareness for betrayal. Participants with histories of high betrayal trauma reported high levels of state dissociation. Contrary to our second hypothesis, high betrayal trauma did not directly predict impaired betrayal awareness. State dissociation contributed significantly to betrayal awareness. Implications of findings for theory and practice are discussed.